(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The objective of this research is to know the ESR mark, through the opinion of consumers and SME companies that obtained the ESR mark during the years 2018, 2019 and 2020. The method used is divided into two parts, In the first, the quantitative data collection method was used, a questionnaire with 23 questions, open, dichotomous, and multiple response was designed, with the aim of knowing what type of consumer was considered regarding the review of the labels, if they look at the logos on the labels, if they identify the product labels and how well did consumers know about the ESR mark? It was sent to the general population, considering the inhabitants of Mexico City and the State of Mexico, through social networks (WhatsApp and Facebook). In the second part, the SMEs that obtained the ESR distinctive were reviewed, during the years 2018, 2019 and 2020, with the publications made by the Mexican Center for Philanthropy (CEMEFI). The main findings are that 29% of consumers are very observant of labels, 69% said they know the ESR badge. 735 SME companies from the years 2018, 2019 and 2020 were reviewed, where between 35%, 41% and 56% respectively show their ESR badge on their Internet page. Future lines of research, which size of micro, small and medium-sized companies are able to obtain, endomarketing studies to find out if companies comply with CSR.